SNFIMCMDA: Similarity Network Fusion and Inductive Matrix Completion for miRNA–Disease Association Prediction - Li, Lei; Gao, Zhen; Zheng, Chun-Hou; Wang, Yu; Wang, Yu-Tian; Ni, Jian-Cheng (Frontiers in Cell and Developmental Biology, 2021)
miRNAs that belong to non-coding RNAs are verified to be closely associated with several complicated biological processes and human diseases. In this study, we proposed a novel model that was Similarity Network Fusion and Inductive Matrix Completion for miRNA-Disease Association Prediction (SNFIMCMDA). We applied inductive matrix completion method to acquire possible associations between miRNAs and diseases, which also could obtain corresponding correlation scores. Inductive matrix completion was performed based on the verified connections of miRNA-disease, miRNA similarity and disease similarity. In addition, miRNA similarity and disease similarity were calculated by similarity network fusion which could masterly integrate multiple data types to obtain target data. We integrated miRNA functional similarity and Gaussian interaction profile kernel similarity by similarity network fusion to obtain miRNA similarity. Similarly, disease similarity was integrated in this way. To indicate the utility and effectiveness of SNFIMCMDA, we both applied global Leave-one-out cross validation and five-fold cross validation to validate our model. Furthermore, case studies on three significant human diseases were also implemented to prove the effectiveness of SNFIMCMDA. The results demonstrated that SNFIMCMDA was effective for prediction of possible associations of miRNA-disease.